The function is
f(x) = (1/3)x² + 10x + 8
Write the function in standard form for a parabola.
f(x) = (1/3)[x² + 30x] + 8
= (1/3)[ (x+15)²- 225] + 8
= (1/3)(x+15)² -75 + 8
f(x) = (1/3)(x+15)² - 67
This is a parabola with vertex at (-15, -67).
The axis of symmetry is x = -15
The curve opens upward because the coefficient of x² is positive.
As x -> - ∞, f -> +∞.
As x -> +∞, f -> +∞
The domain is all real values of x (see the graph below).
Answer: The domain is (-∞, ∞)
Answer:
(8,-3)
Step-by-step explanation:
I just added 1 to the x value and added 2 to the y value because that was the difference between point A and the midpoint of the segment.
Hope this helps!
Answer:
is the answer.
Step-by-step explanation:
Given:
<u>Step 1: Converting the mixed fraction into fraction:</u>
Multiply 4 by 2 add 1 to the result.
<u></u> =
=
=
<u>Step 2: Performing the multiplication using the fraction</u>
= >
=>
<u>Step 3: Converting the product back to mixed fraction </u>
divide 81 by 16 and find the remainder
=>
Dividing 81 by 16 we get 5 as quotient and 1 as remainder
Thus the result in mixed fraction will be
=>
Answer:
x = 1.24
Step-by-step explanation:
In order to get that x down from its current position of exponential, you need to take either the log or the natural log of both sides. The power rule tells us that we can then pull the exponent down in front. So let's take the natural log of both sides:
We can bring the x down in front to give us:
ln(83) = x ln(35)
The right side of this is "stuck" together by multiplication, so we can undo that multilication by division of the ln(35). That leaves us with just x on the right:
Do this on your calculator and find that x = 1.24
If you would like to expand and simplify 3 * (x + 2) + 2 * (x - 1), you can do this using the following steps:
3 * (x + 2) + 2 * (x - 1) = 3 * x + 3 * 2 + 2 * x - 2 * 1 = 5 * x + 6 - 2 = 5 * x + 4
The correct result would be 5 * x + 4.